2011
DOI: 10.2478/v10153-011-0067-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of peripheral vascular resistance in determining the infrainguinal arterial reconstruction patency

Abstract: OBJECTIVE: To fi nd if there is any correlation between the peripheral vascular resistance, its change following an intragraft prostaglandin infusion and the infrainguinal reconstruction patency. PATIENTS AND METHODS: Ninety-seven patients with infrainguinal reconstructions were included in the study: in 48 patients they were compromised (32 with graft thrombosis and 16 with stenosis of the distal anastomoses); 49 patients had their bypasses patent for no less than 12 months. Intraoperative fl owmetry was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Our study confirmed that poor circulation negatively influences the results of both operative and endovascular revascularization. [18][19][20] Another important clinical observation is that when reocclusion occurs in the presence of significant tibial vessel disease, the extent of the thrombus is increased and often precludes any revascularization. Therefore, in our opinion, the presence of poor circulation in patients with ALI warrants aggressive treatment to improve outflow.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed that poor circulation negatively influences the results of both operative and endovascular revascularization. [18][19][20] Another important clinical observation is that when reocclusion occurs in the presence of significant tibial vessel disease, the extent of the thrombus is increased and often precludes any revascularization. Therefore, in our opinion, the presence of poor circulation in patients with ALI warrants aggressive treatment to improve outflow.…”
Section: Discussionmentioning
confidence: 99%
“…Significant efforts are made in intraoperative assessment of results of revascularization procedures. Angiography, measurement of averaged flow, wave form [1][2][3], flow velocity [4,5], resistance [6][7][8][9][10] and impedance [11,12] were used.…”
Section: Introductionmentioning
confidence: 99%